Rancang Model Ontologi untuk Representasi Pengetahuan Senjata Tradisional di Indonesia - I Gusti Agung Gede Ary Mahayasa,; Anak Agung Istri Ngurah Eka Karyawati, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Indonesia is known for its rich diversity, encompassing ethnicity, religion, culture, customs, and traditional artifacts, including traditional weapons. Traditional weapons hold significant historical and cultural value in Indonesia. To preserve and represent knowledge about these traditional weapons, an ontology model is essential. Ontology serves as a knowledge base that can effectively capture and represent information. In this project, we developed an ontology model for traditional weapons in Indonesia using the Protégé ontology development tool. The METHONTOLOGY method guided the step-by-step development of the ontology model, providing detailed descriptions for each stage. The ontology model consists of 6 classes, 4 object properties, 1 data property, and 72 individuals. We conducted testing of the ontology model through SPARQL queries. By building this ontology model, our aim is to contribute to the preservation and documentation of Indonesia's cultural heritage related to traditional weapons. The ontology serves as a valuable resource for researchers, enthusiasts, and institutions interested in studying and promoting traditional weapons in Indonesia.
Keywords: Traditional Waepons, Ontologi, Methontologi, Query SPARQL, Protégé